Prioritization of Museums in Terms of Performance in Attracting Tourists (Case Study: Museum of North of Sistan and Baluchestan Province) - Poodineh, Hossein Saleh; Miri, Gholam Reza; Zadeh, Masume Hafez Reza (International Journal of Geography and Geology, 2016)
Interaction with great cultures and civilizations of ancient times up to now, have enabled Iran to provide the most brilliant science and technology at some points of time to the humanity. In the meantime, Sistan and Baluchestan civilization has a history of several thousands of years, but no effort worthy of this glory have been done to introduce and identify its remained works. Given that the role, development and management of museums have changed greatly in the last two decades, museum institutions, increasingly is being visitor-centered. The aim of this study is to prioritize museums of north of Sistan and Baluchistan province in terms of performance in attracting tourists in the region. The research methods is descriptive – analytical, and data collection has been done through field survey and questionnaire completion, i.e. 350 questionnaires have been completed to assess the Grand Museum of Zahedan, Museum of Zahedan Post-Office, Museum of Zabol Burnt-City (Shahr-e Sukhte) and Anthropology Museum of Zabol. The results of TOPSIS model indicates that the Grand Museum of Zahedan with a score of 0.709 stands in the first place and the Museum of Zahedan Post-Office with 0.235 places at the last of ranking in terms of performance in attracting tourists.